Implementasi Metode Montessori dalam Meningkatkan Hasil Belajar PKn Kelas I SD Negeri 4 Dongos Kedung Jepara - Naim, Jannatun; Widiyono, Aan (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the implementation of the Montessori method, learning outcomes and things that influence the implementation of the Montessori method in improving Civics learning outcomes at SD Negeri 4 Dongos. The research method used is qualitative descriptive. Data collection techniques are interviews, observations and documentation. The analysis method used is crossite analysis. The results of the analysis showed that the implementation of the Montessori method in Civics subjects of grade I semester 1 students of SD Negeri 4 Dongos was quite good. The teacher provides a carefully scientific environment and gives children direction or tutorials in that environment. Teachers constantly monitor children's growth and record their progress so that they can design children's activities to prepare for the next development, step by step. The learning outcomes of Civics at SD Negeri 4 Dongos class I semester 1 of the 2023/2024 academic year are quite good. Factors that influence the implementation of the Montessori method include a negative environment that cannot make student activities to learn, lack of parental supervision for example when students are not in school and lack of attention from teachers other than Civics subject teachers who view Civics subjects as just an ordinary lesson